1987
DOI: 10.1136/jcp.40.3.302
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective evaluation of prognostic value of morphometry in patients with primary breast cancer.

Abstract: SUMMARY In a prospective study the predictive value of a multivariate morphometric prognostic index was evaluated in 195 patients with primary breast cancer who had not been treated with any form of chemotherapy or hormonal treatment. The presence or absence of distant tumour recurrence combined with the scores of the prognostic index were compared with the survival curves predicted in a previous study. The value of the presence of lymph node metastases, number of positive nodes, tumour size, mitotic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In many cancer tissues, including those of the breast, prostate, and pancreas, nuclear morphometry has been reported to be associated with the prognosis or metastatic potential [15, 16, 17, 18]. Mitmaker et al [19]reported that a large nuclear shape factor was a strong risk factor in the prognosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In many cancer tissues, including those of the breast, prostate, and pancreas, nuclear morphometry has been reported to be associated with the prognosis or metastatic potential [15, 16, 17, 18]. Mitmaker et al [19]reported that a large nuclear shape factor was a strong risk factor in the prognosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that proliferation markers are accurate prognostic factors that exceed the prognostic value of classical prognosticators [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. This is especially true for the mitotic activity index (MAI) [5][6][7][8][9][10][12][13][14]16].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for the mitotic activity index (MAI) [5][6][7][8][9][10][12][13][14]16]. Patients with rapidly proliferating tumors have been reported to benefit significantly from ASCT [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16]19 Some of the authors claimed that quantitative morphometric analysis has the capability of measuring nuclear-related variables with objectivity. 11,13,20 Furthermore, it has been reported that morphometric analysis could improve the prediction of prognosis for several malignancies, including carcinomas of the ovary, 21 breast, 22 thyroid, 23 kidney, 24 bladder, 25 stomach, 26 and colon-rectum. 7,[9][10][11][12][13][14][15][16] The NSF determined by nuclear morphometry appeared to have a promising prognostic significance in colorectal carcinoma.…”
Section: Discussionmentioning
confidence: 99%